Quantificação da biomassa e nutrientes em plantios de Eucalyptus urograndis em solos distintos - Salvador, Simone Martini (2015)
This study aimed to obtain information in order to contribute to the nutritional management of Eucalyptus urograndis, based on nutritional characterization, in two different soil types, for the region of Telêmaco Borba - PR. Delimited by 4 parcels located on each floor, making the measurement of all diameters and selection of trees to be felled. The trees were cut at soil level, and the fractionated components: leaves, branch, bark, stem wood, root and ferrule, by collecting a representative sample of each fraction as well as weighed to obtain biomass. To collect the litter were collected 10 samples in each parcels. All the vegetation contained within the floor area of each felled tree (7,5 m2), was regarded as understory which is collected throughout the biomass above and below ground. All biomass samples, understory and litter were sent to the Laboratório, where they were dried at 700C, and after were sent for chemical analysis to determine the macro and micronutrients. The tree biomass total found in the present study was 257,99 Mg ha-1 at a relative contribution of 1,01%; 2,69%; 5,23%; 74,38%; 16,69% F, G, C, M, R, respectively, to the ground soil A. To the soil B in total tree biomass was found 301,21 Mg ha-1 with a compartment relative contribution 1,33% F; 3,80% G; 8,33% C; 74,28% M and 12,27 % of R. The total stock of macro and micronutrients was 1,64 Mg ha-1 for the soil A, with most of the nutrients are found in greater amounts in the compartment wood, except the skin Ca and Fe in the root compartment. For the soil B, the total stock of nutrients was 2,39 Mg ha-1 and most of the nutrients also presented as a higher incidence of compartment wood, except Ca and Mg that are in the bark and B and Fe that are in the compartment roots. The litter presented a biomass in sandy soil 17,35 Mg ha-1, and a total stock of nutrient 335,73 kg ha-1, while for the soil B, biomass was 20,93 kg ha-1 and the total stock of nutrients was 456,76 kg ha-1, and the full magnitude of the amount of macronutrients in litter was N > Ca > Mg > K > S > P, in both soil types. The total biomass found in the understory was 1,08 Mg ha-1 and the total stock of nutrients was 37,96 kg ha-1 for soil A, however, to the soil B, the total biomass was 0,88 Mg ha-1 and the total stock of nutrients was 36,94 kg ha-1, and in both types of soil, the greatest relative contribution of N was 50% for soil A and 53% for the soil B. Among the simulations, the first harvest system the total nutrient exported from the site would be 48% and 57% for sandy and clay soils, respectively, decreasing to 32% in sandy soil and 28% in clay soil to second harvest system and reaching only 20% in sandy soil and 15% in the third clay soil harvest system, causing a reduction of 28% and 42%, respectively examined for each type of soil, thus evident that the harvest system occurs only where the withdrawal of the site is the most suitable wood, which is more sustainable for the site and which could ensure the best nutritional conditions for the next rotation. For the production of all components of the biomass P and Mg elements, the macronutrients are most effectively used in both soil types analyzed, and the coefficient of use for the organic component wood in the following order: P > Mg > S > Ca > N > K for both types of ground studied.